PO057 Risks and benefits of chronic antiepileptic drug treatment. (1st December 2017) - Wieshmann, Udo; Baker, Gus
Abstract : Aim: To estimate risk benefit ratios for anti epileptic drugs (AEDs). Methods: We used the Liverpool adverse event profile (LAEP) as a surrogate marker of risk and the seizure free rate as a marker of benefit in a cohort of 967 epilepsy patients (mono therapy (n=415), poly therapy with 2 AEDs (n=355) and with 3 AEDs (n=197), treatment with Lamotrigine (LTG, n=120), Valproic acid (VPA n=65), Phenytoin (PHT, n=22), Carbamazepine (CBZ, n=97), Levetiracetam (LEV, n=81), Topiramate (TPM, n=12), LTG and VPA (n=18), CBZ and TPM (n=16), CBZ and LEV (n=55), LTG and LEV (n=45), VPA and LEV (n=31), LTG and Clobazam (n=12)). We calculated the risk benefit ratio by dividing the number patients with intoxication (LAEP score >45) with the number of patients who had no seizures in the preceding 4 weeks. Results: The risk benefit ratio was 0.57 for monotherapy, 1.22 for 2 AEDs and 2.33 for 3 AEDs. The risk benefit ratios were LTG and VPA 0.40, LTG 0.46, VPA 0.49, PHT 0.56, CBZ and TPM 0.57, CBZ 0.63, LEV 0.72, CBZ and LEV 0.91, TPM 1.33, LTG and LEV 1.64, VPA and LEV 1.67, LTG and Clobazam 3.00. Conclusion: Mono therapy had a better risk benefit ratio than polytherapy. The differences between AEDs need to be confirmed in larger studies.